2013
DOI: 10.1111/cei.12154
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular mannose-binding lectin deposition is a useful prognostic predictor in immunoglobulin A nephropathy

Abstract: SummaryThere is accumulating evidence to support a hypothesis of the activation of the lectin complement pathway in immunoglobulin A nephropathy (IgAN). The glomerular deposition of mannose-binding lectin (MBL), an initiator of the lectin pathway, has been identified, but its clinical significance has not been defined consistently. The aim of the present study was to investigate the value of glomerular MBL deposition as a useful histological biomarker in evaluating the severity and predicting the prognosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…It is deposited in the renal mesangium and stimulates mesangial cells or activates complement pathways to induce renal damage [31,32]. SIgA is secreted by B cells in mucosal cells, where it enters the circulation and is finally deposited in the mesangium.…”
Section: Discussionmentioning
confidence: 99%
“…It is deposited in the renal mesangium and stimulates mesangial cells or activates complement pathways to induce renal damage [31,32]. SIgA is secreted by B cells in mucosal cells, where it enters the circulation and is finally deposited in the mesangium.…”
Section: Discussionmentioning
confidence: 99%
“…Mesangial deposits of MBL and C4 and/or C4 catabolites are potential markers for the progression of IgAN [103,104]. In contrast, patients with MBL deficiency tend to show better clinical presentation and lower levels of serum creatinine and proteinuria than patients without MBL deficiency [105,106]. N-glycans present on the heavy chains of secretory IgA1 are candidate ligands for lectin pathway activation [107].…”
Section: Mesangial Deposition Of Immune Complexes With Gd-iga1 Cell mentioning
confidence: 99%
“…Zhou et al studied matrix alterations associated with IgAN injury and found that decorin and its analog biglycan -pericellular matrix proteoglycans involved in fibrillogenesis and the regulation of the cell cycle [68] -were increased by 45.1 and 136.6%, respectively [56]. Recognizing this injury, MBL has been proposed to attack damaged and/or apoptotic renal cells, which results in its accumulation in renal tissue and expansion of the mesangial matrix [69]. Immunofluorescence studies on 131 IgAN patients yielded positive staining of MBL in 35% of patients [69].…”
Section: Biomarkers In the Mesangial Matrixmentioning
confidence: 99%
“…Recognizing this injury, MBL has been proposed to attack damaged and/or apoptotic renal cells, which results in its accumulation in renal tissue and expansion of the mesangial matrix [69]. Immunofluorescence studies on 131 IgAN patients yielded positive staining of MBL in 35% of patients [69]. Clinically, MBL deposition results in more severe proteinuria, decreased renal function, lower levels of serum albumin, a greater probability of hypertension and an overall poorer prognosis [69].…”
Section: Biomarkers In the Mesangial Matrixmentioning
confidence: 99%